A Drop in the Ocean. Marine Oil Pollution Preparedness and Response in the Arctic - Lauta, Kristian Cedervall (Arctic Review on Law and Politics, 2017)
This article investigates the Arctic Council’s new Agreement on the response to marine oil pollution in the Arctic Region. The Agreement is evaluated in the light of the challenges of responding to marine oil pollution in the Arctic, and in light of the international legal framework for oil spill response currently in place. Based upon this, the article concludes that the Agreement, rather than being considered an innovative new legal tool, properly is best understood as a symbolic token of the Arctic Council’s willingness to discuss the problems associated with the present plans on resource exploitation in the Arctic. If, however, the Arctic Council sets out to establish an effective legal governance regime to the challenges of responding to a serious oil spill in the Arctic, the Agreement is, as the title suggests, merely a drop in the ocean.